2012
DOI: 10.1111/j.1365-2265.2012.04341.x
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium‐derived factor increases in type 2 diabetes after treatment with metformin

Abstract: Our study is the first to identify a metformin-related increase in PEDF levels in diabetes. The increase observed in PEDF levels after the metformin treatment does not seem to be related to the changes in insulin resistance, fat mass or glycemic control. Hence, our results suggest that further investigation is necessary to determine the direct effects of metformin on PEDF gene and protein expression in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The other candidate, the antidiabetic drug Metformin, exerts an antiproliferative effect on the endometrium of tamoxifen-treated mice via inhibition of mTOR (47). Interestingly, Metformin increases PEDF levels in patients with type II diabetes (48), and our data demonstrated that rPEDF decreased the activity of PI3K/AKT/mTOR pathway. However, inhibition of PEDF by Metformin was described (49), thus further research is needed to fully comprehend the connection among these observations.…”
Section: Discussionmentioning
confidence: 51%
“…The other candidate, the antidiabetic drug Metformin, exerts an antiproliferative effect on the endometrium of tamoxifen-treated mice via inhibition of mTOR (47). Interestingly, Metformin increases PEDF levels in patients with type II diabetes (48), and our data demonstrated that rPEDF decreased the activity of PI3K/AKT/mTOR pathway. However, inhibition of PEDF by Metformin was described (49), thus further research is needed to fully comprehend the connection among these observations.…”
Section: Discussionmentioning
confidence: 51%
“…This is supported by a previous study showing that metformin treatment of patients with newly diagnosed diabetes is associated with a significant increase in serum PEDF level. 20 A great deal of evidence links PEDF to tumor suppression. Besides inhibiting tumor angiogenesis, exogenous or naturally secreted PEDF also induces the differentiation of cancer cells to a less-malignant phenotype, 26,27 which provided the first suggestion that PEDF could reduce malignant phenotype and act directly on tumors.…”
Section: Discussionmentioning
confidence: 99%
“…19 Interestingly, it has been reported that patients with newly diagnosed type 2 diabetes who are taking metformin present higher serum levels of PEDF than those not on metformin. 20 Thus, we hypothesized that the antitumorigenic effects of metformin are mediated through upregulation of PEDF expression in prostate cancer cells. To test this hypothesis, we investigated the effects of metformin on prostate cancer cells and their underlying mechanisms, particularly the involvement of PEDF, both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The vital role of PEDF in diabetic retinopathy has been documented by blocking retinal neovascularization and protecting neural actions on photoreceptors and retinal ganglion cells [11]. Moreover, previous studies have also found that PEDF may play a potentially protective role against tubular injury in diabetic nephropathy by attenuating the deleterious effects of advanced glycation end products via the downregulation of RAGE expression [12,13]. Recently, research has revealed that PEDF can inhibit vascular inflammation [14] and occlusive thrombus formation by blocking platelet activation and aggregation [15] through its anti-inflammatory and anti-oxidative properties [16,17].…”
Section: Introductionmentioning
confidence: 99%